Cloning and characterization of the katA gene of Rhizobium meliloti encoding a hydrogen peroxide-inducible catalase. - Hérouart, D (1996)
To investigate the involvement of bacterial catalases of the symbiotic gram-negative bacterium Rhizobium meliloti in the development of Medicago-Rhizobium functional nodules, we cloned a putative kat gene by screening a cosmid library with a catalase-specific DNA probe amplified by PCR from the R. meliloti genome. Nucleotide sequence analysis of a 1.8-kb DNA fragment revealed an open reading frame, called katA, encoding a peptide of 562 amino acid residues with a calculated molecular mass of 62.9 kDa. The predicted amino acid sequence showed a high homology with the primary structure of monofunctional catalases from eucaryotes and procaryotes. The katA gene was localized on the chromosome, and the katA gene product was essentially found in the periplasmic space. A katA::Tn5 mutant was obtained and showed a drastic sensitivity to hydrogen peroxide, indicating an essential protective role of KatA. However, neither Nod nor Fix phenotypes were impaired in the mutant, suggesting that KatA is not essential for nodulation and establishment of nitrogen fixation. Exposure to a sublethal concentration of H2O2 enhanced KatA activity (100-fold) and also increased survival to subsequent H2O2 exposure at higher concentrations. No protection is observed in katA::Tn5, indicating that KatA is the major component of an adaptive response.